Genetic diversity and population structure of Siganus fuscescens across urban reefs of Seribu Islands, Northern of Jakarta, Indonesia - ADITYA BRAMANDITO; BEGINER SUBHAN; TRI PRARTONO; NURLITA PUTRI ANGGRAINI; HEDI INDRA JANUAR; HAWIS H. MADDUPPA (Biodiversitas Journal of Biological Diversity, 2018)
Bramandito A, Subhan B, Prartono T, Anggraini NP, Januar HI, Madduppa HH. 2018. Genetic diversity and population structure of Siganus fuscescens across urban reefs of Seribu Islands, Northern of Jakarta, Indonesia. Biodiversitas 19: 1993-2002. Jakarta bay and Seribu Islands reefs have been affected by anthropogenic activities which causing them degraded and low quality of the ecosystem. However, lack of study has been conducted to investigate the effect on reef fish population due to change in ecosystem quality. Therefore, this study was undertaken to analyze genetic diversity and population structure of Siganus fuscescens population against heavy metals (Pb, Cd, and Cu) concentration across Jakarta Bay and Seribu Islands environmental gradient. Genetic diversity and structuring of S. fuscescens populations were determined using partial sequences of the mitochondrial cytochrome C oxidase I. Monitoring of heavy metal was measured by Atomic Absorption Spectroscopy (AAS) shows highest concentration of heavy metal (Pb, Cd, and Cu) was observed in the southern of Seribu Islands, closest to Jakarta. However, the diversity of haplotype obtained from each location indicates a varied range between 0,1429 (Pramuka Island, located in the center) and 0,75 (Untung Jawa Island, located in the south). Linear regression test reveals that Cu elements had a moderate effect (R2 adjusted = 0.665) to the nucleotide diversity of the fish. The study shows some populations of S. fuscescens have been affected by heavy metal and could be an alarm to manage this artisanal targeted fish in the Seribu Islands.